External Corrosion Of Pipe Riser API 5L X52 On Tidal Zone Of Offshore Production Platform - Khoirudin, Wakhid Yani; Suyitno, Suyitno (SENATIK STT Adisutjipto, 2019)
External corrosion on mature oil and gas field installation very challenging issues. External corrosion of pipeline riser on tidal zone is the most case for pipeline corrosion [2]. API 5L X52 is familiar pipeline for offshore oil and gas production facilities. Pipeline riser external corrosion on tidal zone have some consequences, time constrain related tidal cycle, production loss, oil spill impact to company reputation, costly maintenance. This research intended to find out effect of tidal cycle and salt water salinity to the rate and type of corrosion on API 5l X52 pipeline riser. Tidal cycle is modeling by wet and dry coupon on salt water. Corrosion rate measure by weight loss coupon. Corrosion product examine by XRD. Chloride contents and oxygen dissolve combination resulting maximum corrosion rate. Oxygen dissolve is main factor to corrosion on salt water. Maximum oxygen dissolve on salt water concentration 3.5% wt. On high salinity salt water corrosion rate depend oxygen dissolve [2]. Tidal cycle has impact to corrosion rate. General corrosion type happen on all coupon with corrosion product component Fe2O3, Fe3O4 examined by XRD.